Cost-effectiveness of sintilimab plus chemotherapy versus chemotherapy alone as first-line treatment of locally advanced or metastatic oesophageal squamous cell carcinoma - Liu, Lulu; Wang, Lei; Chen, Li; Ding, Yiling; Zhang, Qilin; Shu, Yamin (Frontiers in Immunology, 2023)
Background Sintilimab plus chemotherapy significantly prolongs overall survival (OS) for patients with advanced or metastatic oesophageal squamous cell carcinoma (OSCC). However, the cost-effectiveness of this high-priced therapy is currently unknown. We evaluated the cost-effectiveness of sintilimab plus chemotherapy vs chemotherapy alone as fist-line therapy in patients with advanced or metastatic OSCC from the perspective of Chinese healthcare system. Methods A partitioned survival model consisting of 3 discrete health states was constructed to assess the cost and effectiveness of sintilimab plus chemotherapy vs chemotherapy as first-line treatment of OSCC. Key clinical data in the model came from the ORIENT-15 trial. Costs and utilities were collected from published sources. Life-years, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefits (INHB), and incremental net monetary benefits (INMB) were calculated for the two treatment strategies. One-way and probabilistic sensitivity analyses were conducted to account for uncertainty and model stability. Additional subgroup and scenario analyses were performed. Results Treatment with sintilimab plus chemotherapy provided an additional 0.37 QALYs and an incremental cost of 8,046.58 compared with chemotherapy, which resulted in an ICER of 21,782.24 per QALY gained. One-way sensitivity analysis revealed that the model was most sensitive to utility of progression-free survival (PFS) and the cost of sintilimab. The probabilistic sensitivity analysis indicated that the probability of sintilimab plus chemotherapy being cost-effective was 0.01%, 76.80% and 98.60% at the threshold of 1, 2 or 3 times GDP per capita per QALY, respectively. Subgroup analysis found that all subgroups other than PD-L1 expression combined positive scores < 1 subgroup favored sintilimab plus chemotherapy treatment due to its association with positive INHBs by varying the hazard ratios for OS and PFS. The scenario analyses showed altering the time horizon of the model or fitting survival curves separately did not reverse results of the model. Conclusion Sintilimab plus chemotherapy was associated with improved QALYs and an additional cost but was estimated to be cost-effective compared with chemotherapy alone as a first-line treatment for patients with advanced or metastatic OSCC at the commonly adopted willingness-to-pay threshold of 3 times GDP per capita per QALY in China.